Melaleuca Gall Midge (suggested common name) Lophodiplosis trifida Gagné (Insecta: Diptera: Cecidomyiidae: Cecidomyiinae: Cecidomyiini) - Matthew R. Moore; James P. Cuda; Paul D. Pratt; Min B. Rayamajhi (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 6-page fact sheet that discusses the melaleuca gall midge was written by Matthew R. Moore, James P. Cuda, Paul D. Pratt, and Min B. Rayamajhi, and published by the UF Entomology and Nematology Department, July 2016.